2009
DOI: 10.1002/eat.20709
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa: A role for L‐arginine supplementation in cardiovascular risk factors?

Abstract: The results here proposed can be considered highly indicative of a positive effect of L-arginine supplementation on platelet NO production in AN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
2
15
0
1
Order By: Relevance
“…These results extend and confirm previous observations that pointed to enhanced NO production––such as levels of NO metabolites in plasma [1] and in platelets [15]—among patients with AN. The NO overproduction found in AN platelets might be due to iNOS upregulation [15]. However, reports in the literature are scarce and contain conflicting data on the pattern of NO behavior in AN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results extend and confirm previous observations that pointed to enhanced NO production––such as levels of NO metabolites in plasma [1] and in platelets [15]—among patients with AN. The NO overproduction found in AN platelets might be due to iNOS upregulation [15]. However, reports in the literature are scarce and contain conflicting data on the pattern of NO behavior in AN.…”
Section: Discussionsupporting
confidence: 92%
“…However, reports in the literature are scarce and contain conflicting data on the pattern of NO behavior in AN. In contrast to the aforementioned studies [1, 15], Rodrigues-Pereira et al [16] demonstrated diminished NO production in patients with AN, as evaluated by NOS activity and cyclic guanosine monophosphate (cGMP) in platelets.…”
Section: Discussionmentioning
confidence: 96%
“…22,33,34,41 The increase in NO and its metabolites could lead to an increase in RNS that contribute to oxidative stress trough a damage in protein structure. AN subjects showed an increase in NO production, likely due to an increase in iNOS (inducible NO synthase) that leads to high levels of both nitrites and exhaled NO.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore a role of oxidative stress in many neurodegenerative and psychiatric diseases is not surprising. 20 However, data about oxidative stress and antioxidant markers in this disease are scarce, 8,10,21,22 and the low BMI of patients with AN limits the extrapolations from other psychiatric illnesses. 15 Bipolar disorder seems to be associated with increased lipid peroxidation, DNA/RNA damage, and NO compared to healthy controls (HCs).…”
mentioning
confidence: 99%
“…Uno de los tempranos indicadores de deficiencia nutricional en la anorexia nerviosa es la baja concentración plasmática de aminoácidos, como L-arginina, con resultados positivos (relacionados con la producción plaquetaria de óxido nítrico) mediante la suplementación al respecto 64 . En ningún caso, el uso de suplementos puede sustituir a una alimentación normal y tampoco ha mostrado eficacia para mejorar el efecto de la medicación 39 .…”
Section: Uso De Suplementosunclassified